Analysis of the Impact of Predictive Maintenance Based on IoT and Digital Twin on Production Efficiency in the Textile Industry in West Java - Fildansyah, Rully; Sopyan, Sopyan; Novitasari, Salwa Aulia (West Science Social and Humanities Studies, 2025)
This study examines the impact of IoT-based predictive maintenance and digital twin technology on production efficiency in the textile industry in West Java. Employing a quantitative research design, data were collected from 120 respondents using a structured questionnaire with a 5-point Likert scale. Structural Equation Modeling - Partial Least Squares (SEM-PLS) was used for data analysis. The findings reveal that IoT-based predictive maintenance and digital twin technology positively and significantly influence production efficiency. Furthermore, the combined application of these technologies demonstrates the strongest impact, highlighting their synergistic benefits. This study underscores the potential of Industry 4.0 technologies to enhance operational performance in the textile sector and provides actionable insights for industry stakeholders.